Alkaliphilic Bacteria with Impact on Industrial Applications, Concepts of Early Life Forms, and Bioenergetics of ATP Synthesis - Preiss, Laura; Hicks, David B.; Suzuki, Shino; Meier, Thomas; Krulwich, Terry Ann (Frontiers in Bioengineering and Biotechnology, 2015)
Alkaliphilic bacteria typically grow well at pH 9, with the most extremophilic strains growing up to pH values as high as pH 12-13. Interest in extreme alkaliphiles arises because they are sources of useful, stable enzymes, and the cells themselves can be used for biotechnological and other applications at high pH. In addition, alkaline hydrothermal vents represent an early evolutionary niche for alkaliphiles and novel extreme alkaliphiles have also recently been found in alkaline serpentinizing sites. A third focus of interest in alkaliphiles is the challenge raised by the use of proton-coupled ATP synthases for oxidative phosphorylation by non-fermentative alkaliphiles. This creates a problem with respect to tenets of the chemiosmotic model that remains the core model for the bioenergetics of oxidative phosphorylation. Each of these facets of alkaliphilic bacteria will be discussed with a focus on extremely alkaliphilic Bacillus strains. These alkaliphilic bacteria have provided a cogent experimental system to probe adaptations that enable their growth and oxidative phosphorylation at high pH. Adaptations are clearly needed to enable secreted or partially exposed enzymes or protein complexes to function at the high external pH. Also, alkaliphiles must maintain a cytoplasmic pH that is significantly lower than the pH of the outside medium. This protects cytoplasmic components from an external pH that is alkaline enough to impair their stability or function. However, the pH gradient across the cytoplasmic membrane, with its orientation of more acidic inside than outside, is in the reverse of the productive orientation for bioenergetic work. The reversed gradient reduces the trans-membrane proton motive force available to energize ATP synthesis. Multiple strategies are hypothesized to be involved in enabling alkaliphiles to circumvent the challenge of a low bulk proton-motive force energizing proton-coupled ATP synthesis at high pH.